PENGARUH FRAUD HEXAGON, INTERNAL CONTROL, DAN FINANCIAL DISTRESS TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN - Nugroho , Nugroho Inggil; Murtanto, Murtanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This research addresses issues related to the detection of financial statement fraud in non-cyclical consumer companies, focusing on the relationship between the hexagon fraud variables consisting of pressure, opportunity, rationalization, capability, arrogance, and collusions, followed by internal control and financial distress variables on the detection of financial statement fraud as the dependent variable. The analytical method employed by the researcher is multiple linear regression using purposive sampling technique. In this study, the author utilizes secondary data obtained from the annual reports of non-cyclical consumer companies listed on the Indonesia Stock Exchange for the years 2020-2022. From the conducted research, it is concluded that pressure and financial distress variables have a negative impact on the detection of financial statement fraud, while the opportunity variable has a positive influence on the detection of financial statement fraud. On the other hand, rationalization, capability, arrogance, and internal control variables do not affect the detection of financial statement fraud. The findings of this research can serve as a literature reference for future researchers to include citations, methods used, or other relevant information on topics related to and relevant to the opportunity variable that has been proven to have a positive impact in this study. This research contributes to the existing literature by focusing on critical aspects of financial statement fraud detection based on the latest fraud theory, internal control, and financial distress.